PENGHAPUSAN SANKSI PIDANA TERKAIT KEWAJIBAN PEMBERI KERJA UNTUK MENGIKUTSERTAKAN PEKERJANYA DALAM PROGRAM JAMINAN SOSIAL - Hitaningtyas, Ratih Dheviana Puru (Jurnal Panorama Hukum, 2017)
This article aims to analyze the reason of eliminated of criminal sanction on employer obligation to opt in their worker to social security. By using statute approach, conseptual approach and historical approach obtained result that the reason of eliminated of criminal sanction are (i) the inclusion of criminal sanction in previous regulation was ineffective (ii) the eliminated of criminal sanction is in line with the aim of provision of social security, and (iii) the eliminated of criminal sanction is corresponding with the principal of social security.